Soren Kierkegaard’s Concept of Irony in Motojiro Kajii’s Short Story - Fadhila Arienda Humaira; Mumu Muhammad Rifai (Pusat riset dan Inovasi Nasional, 2025)
Motojiro Kajii was a Japanese writer from the early Showa period, born in 1901, who left behind twenty-three great short stories and several other unfinished works, which are always closely related to fundamental questions about life and death, as well as the existence of darkness. Many of Kajii's works contain ironic meanings. Therefore, through a study of irony by Soren Kierkegaard, we describe Motojiro Kajii's thoughts as conveyed in his short story entitled “Sakura ki no shita ni wa”. This research is qualitative research using descriptive research methods. This study will analyse data that shows the explicit or implicit meaning of Soren Kierkegaard's Concept of Irony contained in “Sakura ki no shita ni wa”. The results of the study show that Kierkegaard's concept of irony appears in the short story, such as the negation of the beauty of the cherry blossom tree, but on the other hand, that beauty evokes feelings of restlessness, emptiness and gloom. Beauty does not always bring peace, but rather makes humans aware of transience and the dark side hidden behind something that appears beautiful. Beauty and death are inseparable, and it is thanks to this that beauty is created in life.